REGULATION AND IMPLEMENTATION OF NATIONALITY PRINCIPLES FOR RAPE AND SEXUAL ASSAULT ABOARD - Ramadan, Suta; Seftiniara, Intan; iqbal, Muhammad (Faculty of Law-Universitas Bandar Lampung, 2021)
Sexual violence is an unwanted sexual behavior, such as a request to have sexual intercourse and other sexual behaviors by verbal and physical violence. The problem in this study is how is the legal regulation of rape and sexual assault in Indonesia? and How is the implementation of active national principles for rape and sexual assault crimes that occur abroad? The research method used in this research is normative research method, by examining legal problems using existing literature materials. This study will analyze the legal arrangements for perpetrators of rape and sexual assault crimes to the implementation of the principle of nationality for perpetrators of rape and sexual assaultcrimes that occur abroad. The conclusion in this study is that there needs to be an expansion in the Draft KUHP in regulating criminal acts of immorality, especially rapes committed similarly, both carried out by men and women and the application of the principle of personality both active and passive can be given by the state if the crime is related to the interests of the state, and the existence of bilateral agreements between the two countries so that legal diplomacy can run smoothly until it gets the best way out.